Clothes Thrifting Purchase Intention among Muslim Students in Bandung: Moderating Role of Legal Awareness and Islamic Consumption Ethics - Rizky Andrean; Rudy Heryana; Muhammad Khoirul Fikri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines the determinants of purchase intention toward illegally imported second-hand clothing (clothes thrifting) among Muslim university students in Bandung, Indonesia, with specific attention to the moderating roles of legal awareness and Islamic consumption ethics. Employing a quantitative survey design, data were collected from 216 respondents through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study addresses a novel intersection in the literature by testing whether religiously grounded ethical frameworks and regulatory knowledge function as behavioral moderators in the context of a legally prohibited consumer market. The results demonstrate that price, brand image, and lifestyle each exert a significant positive effect on purchase intention toward illegally imported second-hand clothing. Critically, both legal awareness and Islamic consumption ethics significantly weaken these relationships, functioning as normative and ethical constraints on consumer behavior. These findings contribute empirical evidence to the intersecting literatures of consumer behavior, Islamic economics, and regulatory compliance. This study advocates an integrative policy approach that leverages Islamic legal education and ethical literacy to direct consumer behavior toward legitimate and domestically oriented fashion consumption.